Use of Lateral Access in the Treatment of the Revision Spine Patient. (10th December 2012) - Bederman, Samuel S.; Le, Vu H.; Pahlavan, Sohrab; Kiester, Douglas P.; Bhatia, Nitin N.; Deviren, Vedat
Abstract : With the rate of spinal surgery increasing, we have seen a concomitant increase in the number of revision cases. It is, therefore, important to have a systematic approach to the management of these complicated patients with unique problems. A thorough understanding of the different pathologies affecting revision spine patients is critical to an effective treatment recommendation. Lateral access is a useful management approach since it can avoid the complications of operating through previous approaches. Furthermore, it possesses certain advantages for treatment in specific circumstances outlined in this paper. Long-term studies are needed to demonstrate the safety and efficacy of the lateral approach compared to the anterior and posterior approaches in the treatment of revision spine patients.